Effects of spraying lactic acid and peroxyacetic acid on the quality and microbial community dynamics of vacuum skin-packaged chilled beef during storage. (April 2021) - Han, Jina; Liu, Yunge; Zhu, Lixian; Liang, Rongrong; Dong, Pengcheng; Niu, Lebao; Hopkins, David L; Luo, Xin; Zhang, Yimin
Graphical abstract: Highlights: The quality traits of VSP beef were evaluated after 3% lactic acid spray before packaging (LLA). LLA samples exhibited the lowest TVBN and TVC values during the storage of 32 days. LLA showed the best antibacterial potential without any deleterious effects on the VSP chilled beef. This is attributed to the reduction of Proteobacteria and B. thermosphacta of LLA beef steaks. Abstract: A long shelf life for fresh meat products is very important both to processors, retailers and consumers. In this work, the effect of repeat acid spraying on the shelf life of vacuum skin-packaged (VSP) chilled beef, as well as the quality and microbial community dynamics was evaluated. Carcasses were sprayed with 300 ppm peroxyacetic acid (PA) or 3% lactic acid (LA) three times during the chilling process, or one more time of LA spray before packaging (LLA). Quality, sensory attributes and microbial load of VSP beef during 32 days of storage at 4 °C were evaluated. The results showed that quality and sensory scores decreased over time for all treatments, but LLA treated samples were still above the rejection threshold at the end of the storage period. Moreover, the total volatile basic nitrogen value and the total viable counts were 15.0 mg/100 g and 7.2 log CFU/g for the control group, while acid treated groups remained below these two values until the end of the storage period. In particular LLA treated beef steaks exhibited the best preservation potential even at the end of storage. This is attributed to the reduction of Proteobacteria in LLA beef steaks shown by the bacterial diversity analysis via high-throughput sequencing, as well as the lower counts of B. thermosphacta and Enterobacteriaceae during storage. This indicates that LLA treatment has the potential to achieve a shelf life extension of VSP steaks without impacting on quality.